Rehabilitation of gymnasts - Tilley, D.; James, D. A. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
The sport of gymnastics is one of the most impressive and demanding displays of athleticism. It requires gymnasts to possess a unique blend of sport qualities including strength. explosive powcr. flexibility, coordination, balance, and metabolic capacity that is unlike any other sport. Alongside the large physical demands, it also requires an extraordinary amount of mental toughness, emotional capacity, and discipline. This is due to the high-risk nature of the skills trained, the presence of young children being exposed to high-level skills, and the large time commitment required over many years to achieve progress. Due to this mosaic of factors, the rehabilitation process for gymnasts is often seen as an enigma to the medical field. The combination of high forces, extreme ranges of motion, high repetition, and high training vvorkloads in young athletes who have not fully matured, all present a significant challenge. As discussed in previous chapters, there is a growing body of research and literature regarding injury incidence and common injury patterns within the sport. However, there is a paucity of research and peer-reviewed literature regarding the best methods of rehabilitation, return to sport, and injury prevention. although recent papers have begun the process of creating formalized protocols. Due to the lack of available peer-reviewed literature, it is necessary to utilize a combination of anatomy, physiology, and movement Science literature from other fields as a base. From here, the current gymnastics biomechanical and epidemiology data can be layered on top of rehabilitation principles to extrapolate best practices. A large chasm in the continuum of care exists within gymnastics sports medicine in that gymnasts often do not receive the sports-specific rehabilitation needed to return safely to training. When a lack of advanced rehabilitation is combined with a lack of systematic and validated return to sport progressions, gymnasts are often left stuck in the "gap" betvveen traditional rehabilitation and sport training, frequently yielding high rates of reinjury and ongoing pain. This often leads to the stacking of multiple injuries early in one's career. chronic reinjury, and mental health burden. Due to this, far too many gymnasts may not reach their full athletic potential, may continue to accumulate injuries, or may quit the sport as a result. A recent review determined that injury rates in gymnastics ränge from 1.08 to 50.3 occurrences per 1000 hours of exposure, and are most common in the lower extremity (ankle sprains and internal knee derangements in particular, with the exception of male artistic gymnasts suffering more shoulder injuries). Of particular importance. the rehabilitation Professional must take note of lumbar spine injuries in female gymnasts, shoulder and wrist injuries in male gymnasts, and lower body impact injuries in both genders, as these continue to be issues that plague gymnasts worldwide. These areas of the body require additional attention due to their prevalence, as well as their potentially deleterious effects on long-term health and performance.